On the genus Sunius Curtis, 1829 of Turkey II. Two new micropterous species and additional records from Western Anatolia (Coleoptera: Staphylinidae: Paederinae) - Anlaş, Si̇nan (Zootaxa, 2015)
Two new species of the genus Sunius Curtis, 1829 are described from Denizli province of Western Anatolia and illustrated: Sunius yagmuri sp. n. from Akkaya Hill and Sunius golgeliensis sp.n. from Gölgeli Mountains. Additional records of five species of Sunius are reported. A total of 32 species are now known from Turkey, 28 of them are endemic.